Pengaruh Arus Kas Operasi, Profitabilitas dan Corporate Governance terhadap Return Saham - Randi Kurniawan, (2021)
This study aims to determine the effect of operating cash flow, profitability and corporate governance on stock returns in manufacturing companies listed on the Indonesia Stock Exchange in the 2018-2020 period. This research is a type of quantitative research that uses secondary data in the form of company annual reports. This study used a sample of 60 manufacturing companies. The technique for analyzing the data in this study uses a regression model selection test, classical assumption test, panel data regression, and partial hypothesis testing (t test). Based on the results of data analysis, it can be concluded that (1) operating cash flow has no effect on stock returns, (2) profitability has no effect on stock returns, (3) corporate governance has a significant effect on stock returns.